Immune Response and Susceptibility to SARS-CoV2 Virus in Children - Merchan, Maritza Angarita; Silva, Rosa Isela Neira; Velandia, Diana Paola López (International Journal of Pediatrics and Child Health, 2021)
The COVID-19 disease that was first discovered in Wuhan-China province, also called severe acute respiratory syndrome, is a serious public health concern in the 21st century. This disease affects the respiratory system and its causal agent is the SARS-CoV2 virus, which is part of the family of beta-corona viruses that many associate with the bat. This virus not only affects the population that is considered vulnerable but also affects young adults and children. The objective of the present review is to describe the characteristics of the immune response and susceptibility in children with SARS-COV2. We examined articles in the Elsevier, Google Scholar, PubMed and Scielo databases regarding the immune systems of children with the disease of COVID-19 and the physio-pathological mechanisms of SARS-CoV2 that contribute to illness in this population. Although the capacity of infection of SARS-CoV2 in children is very high, the mechanism of the virus against pathogenicity in this population group is not clear. The objective of the present review is to describe the characteristics of the immune response and susceptibility in children with SARS-COV2.